Mediating Role of Affective Commitment in the Relationship between HRM Practices and Employee Engagement in the Context of Surabaya’s Millennial Workforce in the Manufacturing Sector - Felicia Trifena Christanto (iBuss Management, 2020)
Manufacturing sector is believed to be the sector that will drive Indonesia’s economic growth. However, millennial employees, which are the least engaged employees, are begin to dominate this sector. Human Resource Management (HRM) practices such as career advancement, performance feedback, job security, training and development, rewards and recognition, and employee participation are said to be the significant predictors of employee engagement. In addition, the relationship between HRM practices and employee engagement is mediated by affective commitment. The objective of this research is to identify the influence of HRM practices received by Surabaya’s millennial workforce in the manufacturing sector to their engagement. This research also aimed to find out whether or not mediation effect of affective commitment exists.Online questionnaire was distributed to 120 qualified respondents. The data gathered has passed validity, reliability, and classical assumption tests. Through using multiple regression analysis and Sobel test, this research proved that performance feedback, job security, training and development, and rewards and recognition are individually significant to employee engagement of Surabaya’s millennial workforce working in the manufacturing sector. Moreover, it turns out that affective commitment partially mediates the relationship between training and development and employee engagement.Keywords: Employee Engagement, Human Resource Management Practices,Affective Commitment, Millennial, Manufacturing Sector